2022
DOI: 10.1002/jssc.202200589
|View full text |Cite
|
Sign up to set email alerts
|

A model for continuous sample feed and separation with counter‐current chromatography based on elution‐extrusion mode and its application

Abstract: A novel and meaningful theoretical model was established with counter-current chromatography based on the elution-extrusion mode for efficient continuous separation. For the experimental verification of the theory, the separation of the binary mixture luteolin/baicalein was studied. The velocity model and volume model of the chromatographic separation behavior of the target compounds in the separation process were given by theoretical analysis. The results showed that this method had obvious advantages in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Consequently, this approach holds the potential to substantially reduce time requirements and diminish solvent consumption. In this method, the continuous injection time (T inj ) emerges as a crucial parameter as it dictates the maximum loading capacity during the countercurrent chromatographic separation [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this approach holds the potential to substantially reduce time requirements and diminish solvent consumption. In this method, the continuous injection time (T inj ) emerges as a crucial parameter as it dictates the maximum loading capacity during the countercurrent chromatographic separation [23].…”
Section: Resultsmentioning
confidence: 99%
“…This study introduces a continuous separation method based on the elution-extrusion mode, aimed at enhancing the separation efficiency of HSCCC [23]. The established continuous HSCCC method offers the greatest advantage of allowing for the continuous pumping of the sample solution into the separation process, eliminating the need for re-establishing dynamic equilibrium and multiple injections.…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of reduced separation time and solvent consumption, EECCC mode was introduced to use sweeping elution and extrusion for the full use of the liquid nature of the stationary phase [26]. EECCC mode could cover an extended polarity range of solutes and could save time for the big K D value compound separation [27]. So, compound 3 was separated in EECCC mode, while compounds 1 , 2 , 3 , and 6 were further separated by prep‐HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the feasibility of the use of HPCCC as an industrial method to obtain these metabolites, evaluation of processes that allows continuous injection of higher volumes of extracts to increase the yield without increasing the solvent consumption and separation time should be investigated for winemaking by-product extracts. This approach has been previously applied to isolate high-purity oleuropein from olive leaf extract [ 41 ]. The protocol presented by the authors showed advantages for separating binary mixtures of compounds, such as the large-scale purification of a high-content target compound in the extracts.…”
Section: Resultsmentioning
confidence: 99%